2022
DOI: 10.3389/fimmu.2022.954848
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Experimental Validation of Rheumatoid Arthritis Innate Immunity Gene CYFIP2 and Pan-Cancer

Abstract: Rheumatoid arthritis (RA) is a chronic, heterogeneous autoimmune disease. Its high disability rate has a serious impact on society and individuals, but there is still a lack of effective and reliable diagnostic markers and therapeutic targets for RA. In this study, we integrated RA patient information from three GEO databases for differential gene expression analysis. Additionally, we also obtained pan-cancer-related genes from the TCGA and GTEx databases. For RA-related differential genes, we performed functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 68 publications
0
19
0
Order By: Relevance
“…Currently, studies applied WGCNA were normally combined with multiple machine learning algorithms to identify biomarkers for disease prognosis and diagnosis. Zhao et al (2022) identified four core genes (BTN3A2, CYFIP2, ST8SIA1, and TYMS) as biomarker for diagnosis of rheumatoid arthritis via comprehensive analysis of WGCNA, LASSO, random forest, and support vector machine analysis. By WGCNA, LASSO, and random forest algorithms, Fan et al (2022) obtained five signature genes (UPP1, S100A9, KIF1B, S100A12, SLC26A8) and emerged remarkable diagnostic performance in pediatric septic shock.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, studies applied WGCNA were normally combined with multiple machine learning algorithms to identify biomarkers for disease prognosis and diagnosis. Zhao et al (2022) identified four core genes (BTN3A2, CYFIP2, ST8SIA1, and TYMS) as biomarker for diagnosis of rheumatoid arthritis via comprehensive analysis of WGCNA, LASSO, random forest, and support vector machine analysis. By WGCNA, LASSO, and random forest algorithms, Fan et al (2022) obtained five signature genes (UPP1, S100A9, KIF1B, S100A12, SLC26A8) and emerged remarkable diagnostic performance in pediatric septic shock.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our previous whole-exome sequencing showed that various genes are frequently mutated in primary tumors and CTCs ( 19 ). Of these mutated genes, some are well-characterized functional oncogenes, such as CYFIP2 , NOP16 , and ZNF117 ( 28 ā€“ 30 ), and genetic variations in others are closely associated with other cancers, such as MOB3C and SSPO ( 31 , 32 ). It was also found that non-silent single nucleotide variations (non-silent SNVs) and insertion-deletion mutations were more frequent in CTCs than in primary tumor samples ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…gmt" datasets to investigate the various levels of infiltration of immune cell types between SLE samples and normal samples. [21] A single-sample gene set enrichment analysis (ssGSEA) is a particular type of analysis that combines the "immune. gmt" dataset with the ssGSEA method.…”
Section: Immune Infiltration Analysis By Ssgseamentioning
confidence: 99%